2012
DOI: 10.1136/oemed-2011-100561
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and predictors for respiratory illnesses and symptoms and lung function among textile workers in Karachi, Pakistan

Abstract: This study highlights the burden of respiratory illnesses and symptoms, and a low prevalence of asthma among textile workers in Karachi. Work in the spinning section, lack of education, prolonged duration of work and Sindhi ethnicity, were identified as important risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 28 publications
9
41
1
4
Order By: Relevance
“…12,13 The exposed workers had more respiratory symptoms such as chronic cough, phlegm, chest tightness, and dyspnea. The prevalence of symptoms in the current study was comparable to the findings of Nafees, et al, 10 who found that 7.5% and 12.9% of cotton workers had chronic cough and chronic phlegm, respectively. Nevertheless, they found a significantly higher prevalence of wheeze and shortness of breath (22.3%) compared to ours.…”
Section: Discussionsupporting
confidence: 80%
“…12,13 The exposed workers had more respiratory symptoms such as chronic cough, phlegm, chest tightness, and dyspnea. The prevalence of symptoms in the current study was comparable to the findings of Nafees, et al, 10 who found that 7.5% and 12.9% of cotton workers had chronic cough and chronic phlegm, respectively. Nevertheless, they found a significantly higher prevalence of wheeze and shortness of breath (22.3%) compared to ours.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies30 31 in the cotton mills in Pakistan reported respiratory symptoms from the large weaving and spinning factories. For the first time, we performed PF tests on workers in small-scale household weaving factories compared to a sample of workers from large weaving units.…”
Section: Discussionmentioning
confidence: 96%
“…Some of the subjects reported about asthma (5%) during their childhood and we could not find a subject of asthma in the workplace (cf. Tanzil and Nafees (2015) Nafees et al (2013)). …”
Section: Discussion:-mentioning
confidence: 99%
“…In above mentioned context some studies were carried out in Karachi, Pakistan to discuss burden of respiratory problems among textile worker but more detailed studies are required in Punjab, Pakistan such as Nafees et al (2013;Tanzil and Nafees (2015)). So the aim of this cross sectional study was to describe chronic respiratory symptoms and lung function impairment, and their relations with socio-demographic factors, exposure to cotton dust and in a composite textile processing unit in the Punjab.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation